Frequency of Lympnode Metastasis in Supraglottic Ca Larynx - Bhuiyan, Mohammad Rokan Uddin; Ali, Mohammad Idris; Siddiquee, Balayet Hossain; Johora, Fatema; Hossain, Mohammad Kamal (Medicine Today, 2019)
Introduction: To observe the association between the level of lymph node metastasis and the T- stage and to evaluate the N- stage in supraglottic carcinoma of larynx. Materials and Methods: A prospective cross-sectional study was carried out on 80 consecutive cases of supraglottic carcinoma larynx in three tertiary level hospital in Dhaka during July'2009 to March 2011. Results: The highest number of patients were in the age group 5th and 6th decades. Male to female ratio was 9:1. Topographically 70 cases (87.5%) had lesions involving epiglottis, 5 cases (6.25%) in aryepiglottic fold and 5 cases (6.25%) had lesions at false cord. Majority cases were histopathologically confirmed squamous cell carcinoma (95%) and among them 46 cases (57.5%) had well differentiated. Cervical metastatic lymph nodes were found 40% (32 cases) where level-II was most common. This was most frequent in early supraglottic(T1&T2) carcinoma of larynx (86.25%), P=0.008. A positive correlation was found between the T stage of primary tumours and frequency of cervical lymphadenopathy. Lymph node metastasis were 4.77% in T1, 37.50% in T2, 71.43% in T3 and 91.67% in T4. In early stage lymph node involved 93.75% in Level- II, 6.25% in Level- III & in advanced stage 100% in Level - II, 62.5% in Level - III and 25.0% in Level - IV. Distribution of study cases (31.25%) in stage-II, 25% in stage-I, 22.50% in stage-Ill and 21.25% were in stage-IV. Conclusion: Result of this study may help the clinician for planning of treatment of this malignant diseases as well awareness. Medicine Today 2019 Vol.31(2): 72-75